Maternal Sensitivity Modulates Child’s Parasympathetic Mode and Buffers Sympathetic Activity in a Free Play Situation - Köhler-Dauner, Franziska; Roder, Eva; Gulde, Manuela; Mayer, Inka; Fegert, Jörg M.; Ziegenhain, Ute; Waller, Christiane (Frontiers in Psychology, 2022)
Background Behavioral and physiological (self-)regulation in early life is crucial for the understanding of childhood development and adjustment. The autonomic nervous system (ANS) is a main player in the regulative system and should therefore be modulated by the quality of interactive behaviour of the caregiver. We experimentally investigated the ANS response of 18- to 36-month-old children in response to the quality of maternal behavior during a mother-child-interacting paradigm. Method Eighty mothers and their children came to our laboratory and took part in an experimental paradigm, consisting of 3 episodes: a resting phase (E1), a structured play phase (E2), and a free play situation (E3) between mothers and their child. Children's and mother´s heart rate (HR), the sympathetic nervous system (SNS) activity via the pre-ejection period (PEP) and the left ventricular ejection time (LVET), and the parasympathetic nervous system (PNS) activity via the respiratory sinus arrhythmia (RSA) were continuously measured by an electrocardiogram. Maternal sensitivity of interactive behavior was assessed by using the Emotional Availability (EA) Scales. Results Children of mothers with insensitive behavior had a significantly lower RSA at baseline, showed a lack of RSA withdrawal during structured and free play and had shorter LVET across all episodes compared to children of sensitive mothers. Conclusions Our findings depict the influence of low-quality maternal interaction on the child´s ANS regulation, in calm and more stressful play situations. The overall higher SNS mode with impaired PNS reactivity may negatively influence child’s ANS homoeostasis, which may result in a long-term impact on mental and physical well-being. Further, the maternal sensitivity may function as a buffer for the stress response of their child. These results could serve as a basis for the development of appropriate psychoeducational programs for mothers of low sensitivity in their interaction with the child.